Effect of Phosphorus Levels and PSB on Spring Maize Performance in Surkhet, Nepal - Shah, Binod Prasad; Sharma, Raksha; Niraula, Satya; Kushwaha, Niranjan (Far Western Review, 2025)
A field experiment was conducted to evaluate the performance of spring maize var. Arun-2, under different levels of phosphorous with phosphate solubilizing bacteria (PSB) in Gurbhakot Municipality-09, Surkhet district from February to July 2023. For this study, randomized complete block design (RCBD) was implied with six treatments and four replications. Treatments included different levels of phosphorus fertilizer (P2O5) and PSB viz. T1 (0kg P2O5+PSB/ha), T2 (30kg P2O5+PSB/ha), T3 (60kg P2O5+PSB/ ha), T4 (90kg P2O5+PSB/ha), T5 (120kg P2O5+PSB/ha) and T6 (60kg P2O5/ha without PSB as RDF). The result showed significant effect of phosphorous on growth, phenology, yield attributing traits and yield of maize at 5% level of significance, except for 1000 grain weight. Days to 75% tasseling, silking and maturity significantly decreased with the increasing level of phosphorus, whereas plant height and number of leaves increased with increasing dose of phosphorous. However, cob length, number of grains per cob and grain yields were found to be the highest in T3 and the lowest in T1. Similarly, application of phosphorous @60 kg/ha along with PSB could be suggested for maximizing yield of spring maize (Arun-2) in the agro-ecological conditions of Surkhet.